PENGARUH KUALITAS INFORMASI AKUNTANSI, PERSEPSI KONTROL PERILAKU, DAN PENGETAHUAN INVESTASI TERHADAP INTENSI INVESTOR DALAM PEMILIHAN SAHAM DI GI-BEI UNIVERSITAS TRIATMA MULYA - Luh Lia Maharani; I Ketut Yudana Adi (Universitas Triatma Mulya, 2021)
This study aims to determine the effect of the quality of accounting information, perceptions of behavioral control, and knowledge of investment on investor intentions in stock selection at Galeri Investasi Bursa Efek Indonesia Universitas Triatma Mulya. The population of this study is the investor of GI-BEI Universitas Triatma Mulya. Samples taken based on non-probability sampling technique using questionnaires as many as 40 respondents. The method of analysis is done using Multiple Linear Regression Analysis. The results showed that the quality of accounting information has a positive and significant effect on investor intentions in stock selection, behavior control perceptions have a positive and significant effect on investor intentions in stock selection, and knowledge of investment has a positive and significant effect on investor intentions in stock selection.